Growing Heirloom Tomato Varieties in Southwest Florida - Monica Ozores-Hampton; Charles S. Vavrina; Aline Coelho Frasca (EDIS, 2012)
Heirloom tomatoes have seen a rebirth in popularity because of increasing demand for fresh, fully ripe, tasty tomatoes. A tomato must meet three criteria to be considered an heirloom variety: The variety must be reproduced by seed, must have been cultivated for more than 50 years, and must have a history. Heirloom tomatoes are known for their singular taste, shape, and color, which include purple, orange, and yellow, in addition to the common red tomatoes. This revised 9-page fact sheet was written by Monica Ozores-Hampton, Charles S. Vavrina, and Aline Coelho Frasca, and published by the UF Department of Horticultural Sciences, February 2012.